Specific binding of cruciform DNA structures by a protein from human extracts. - Elborough, K M (1988)
A gel electrophoresis binding assay has been used to probe extracts from cultured human lymphoblasts for proteins that bind cruciform structures in duplex DNA. Proteins have been detected that form complexes with synthetic X- and Y-junctions. Several lines of evidence suggest that binding is specific for DNA structure rather than sequence: (1) X- and Y-structures were bound whereas linear duplexes containing identical DNA sequences were not, (2) Binding occurred with equal efficiency to two X-junctions that were constructed from DNA strands of different sequence, (3) One X-junction successfully competed with another for binding whereas linear duplex DNA did not; and (4) protein-DNA complexes were observed at probe:non-specific competitor DNA ratios of 1:10,000.